The effect of deep breathing exercise on chest pain in tuberculosis patients - Nurul Aini Rahmawati; Erfil Refilda; Atika Yulianti (Physical Therapy Journal of Indonesia, 2023)
Background: Tuberculosis (TB) is a disease transmitted by Mycobacterium tuberculosis. One of the clinical manifestations of this disease is the presence of chest pain that is felt. Chest pain in TB patients can be reduced by practising deep breathing exercises. Methods: This quantitative research with a quasi-experimental design used the one-group pre-test and post-test method with 25 samples. Breathing exercises in the intervention were given four times a week for one month. The numeric rating scale (NRS) measures the value of chest pain. Results: Based on the Wilcoxon statistical test, the effect of breathing exercise significantly reduced the chest pain with p=0.000, α= 0.050. Conclusion: There is an effect of deep breathing exercises on chest pain in TB patients in the Dau district.